Pilularia ethiopica (Pteridophyta, Marsileaceae), a new species of pillwort from the tropical African mountains of Ethiopia - Fischer, Eberhard; Killmann, Dorothee; Ackermann, Markus; Yeshitela, Kumelachew (Phytotaxa, 2023)
Pilularia ethiopica is described as a new species from the highlands of Ethiopia. It is similar to P. americana, P. bokkeveldensis, and P. dracomontana, but differs from P. americana in the shorter fronds, the smaller sporocarp, the shorter pedicel, and the subterranean sporocarps at maturity. It differs from P. bokkeveldensis in the obvious circinate vernation, the smaller sporocarps, the shorter pedicel, and the subterranean sporocarps at maturity. It differs from P. dracomontana in the longer fronds, the obvious circinate vernation, the longer pedicel, and the only partly submerged habit.